2018
DOI: 10.1123/jcsp.2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, Burnout, and Depression in Youth Soccer Players: A Longitudinal Study

Abstract: The relationship between perfectionism, burnout and depression among youth soccer players is of interest due to the stressful academy environments that must be navigated in order to become a professional soccer player. Three alternative theoretical models have been proposed to explain the relationship between perfectionism, burnout and depression. These models state that perfectionism is (a) a vulnerability factor for burnout and depression (vulnerability Researchers have recently begun to examine the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
0
24
2
2
Order By: Relevance
“…Hill, Hall, Appleton, & Kozub, 2008), longitudinal evidence indicates that it may be unrelated to burnout over time (e.g. Smith et al, 2018). In contrast, researchers have consistently found that socially prescribed perfectionism is positively related to athlete burnout (e.g.…”
Section: Athlete Perfectionism and Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill, Hall, Appleton, & Kozub, 2008), longitudinal evidence indicates that it may be unrelated to burnout over time (e.g. Smith et al, 2018). In contrast, researchers have consistently found that socially prescribed perfectionism is positively related to athlete burnout (e.g.…”
Section: Athlete Perfectionism and Burnoutmentioning
confidence: 99%
“…Other-oriented perfectionism has typically been excluded from these studies as it has been viewed as less important to the development of burnout (cf. Smith et al, 2018). This omission originates from the assertion that otheroriented perfectionism is an interpersonal dimension that has less relevance to self-referenced or personal outcomes (Hewitt & Flett, 1991).…”
Section: Athlete Perfectionism and Burnoutmentioning
confidence: 99%
“…The second reason is that they are empirically distinct. In sport, there are three studies that have examined the correlation between burnout and depression in athletes (N = 856; Cresswell & Eklund, 2006;Raedeke et al, 2013;Smith et al, 2018). On average, across the symptoms of burnout, this correlation is around .50.…”
Section: Is Burnout More Than Depression?mentioning
confidence: 99%
“…Moreover, this may further negatively impact one’s health status in their adulthood. Recently, a few studies were conducted using a longitudinal study design in youth soccer players, especially the injury incidence [ 26 ], a relationship of peak high velocity and performance [ 27 ], and, also psychological factors in adolescent soccer players [ 28 ]. However, no study had investigated the long-term progression of such specific factors as foot morphology, BW distribution, and PS in young professional soccer players.…”
Section: Introductionmentioning
confidence: 99%